Anterior Vertebral Body Tethering for Adolescent Scoliosis with Growth Remaining: A Retrospective Review of 2 to 5-Year Postoperative Results. (1st July 2020) - Hoernschemeyer, Daniel G.; Boeyer, Melanie E.; Robertson, Madeline E.; Loftis, Christopher M.; Worley, John R.; Tweedy, Nicole M.; Gupta, Sumit U.; Duren, Dana L.; Holzhauser, Christina M.; Ramachandran, Venkataraman M.
Abstract : Background: Anterior vertebral body tethering (VBT) is an early treatment option for progressive scoliosis in pediatric patients, allowing for continued deformity correction during normal growth. We report postoperative radiographic and clinical outcomes for patients treated with VBT. Methods: This clinical and radiographic retrospective review of 31 consecutive patients included an analysis of preoperative, perioperative, and postoperative details, including the Lenke classification; Cobb angle measurements of the proximal thoracic, main thoracic, and lumbar curves; the sagittal profile; and skeletal maturity. Successful outcomes were defined by a residual curve of ⩽30° in skeletally mature patients who did not undergo a posterior spinal fusion (PSF). Results: Of the 31 patients treated, 29 met the inclusion criteria, and 2 were lost to follow-up. The mean patient age (and standard deviation) at the time of the surgical procedure was 12.7 ± 1.5 years (range, 10.2 to 16.7 years), with most patients classified as Risser grade 0 or 1 (52%) and Sanders stage 3 (32%). A mean of 7.2 ± 1.4 vertebral levels were instrumented, with a minimum preoperative Cobb angle of 42°. At the latest follow-up, 27 patients had reached skeletal maturity (Sanders stage ≥7) and 20 patients exhibited a curve magnitude ⩽30°, for a success rate of 74%. A suspected broken tether occurred at ≥1 level in 14 patients (48%). Two patients underwent PSF and 4 had tether revision. The overall revision rate was 21% (6 of 29). Conclusions: This study shows the success and revision rates as well as the impact of a suspected broken tether on the procedural success of VBT. Despite our patient population being slightly more mature at the time of the surgical procedure compared with previous studies, we had a higher success rate and a lower revision rate. A PSF was avoided in 93% of patients, indicating that VBT may be a reliable treatment option for adolescent scoliosis in skeletally immature individuals. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.